Inside Cover: A Chemo‐Enzymatic Approach for Site‐Specific Modification of the RNA Cap (Angew. Chem. Int. Ed. 30/2013). Issue 30 (21st June 2013) - Schulz, Daniela; Holstein, Josephin Marie; Rentmeister, Andrea
<x xml:space="preserve">Abstract</x> Targeting the mRNA cap by a chemo‐enzymatic approach opens up new possibilities in mRNA isolation and visualization. In their Communication on page 7874 ff. A. Rentmeister and co‐workers present a novel two‐step approach for the regiospecific labeling of the m7G cap, a hallmark of eukaryotic mRNAs. They make use of a trimethylguanosine variant capable of transferring reactive groups from AdoMet analogues to the cap. The transferred residues are amenable to click reactions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>